Dayside and nightside contributions to the cross polar cap potential: placing an upper limit on a viscous-like interaction - S. E. Milan (Annales Geophysicae, 2004)
Observations of changes in size of the ionospheric polar cap allow the dayside and nightside reconnection rates to be quantified. From these it is straightforward to estimate the rate of antisunward transport of magnetic flux across the polar regions, quantified by the cross polar cap potential ΦPC. When correlated with upstream measurements of the north-south component of the IMF, ΦPC is found to increase for more negative Bz, as expected. However, we also find that ΦPC does not, on average, decrease to zero, even for strongly northward IMF. In the past this has been interpreted as evidence for a viscous interaction between the magnetosheath flow and the outer boundaries of the magnetosphere. In contrast, we show that this is the consequence of flows excited by tail reconnection, which is inherently uncorrelated with IMF Bz.